HUKUM KEPEMIMPINAN POLITIK PEREMPUAN (Studi Terhadap Perspektif Muballigh Pekanbaru Riau) - Akabrizan Akbarizan Akbarizan (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Election of Pekanbaru mayor is a phenomenon because one candidates is a woman and Islamic law used to attack political opponents. The purpose is to find out how according to Islam, the opinion of Riau preachers on women's leadership, the postulates of Islamic law that they use, and views on Pekanbaru mayor candidate, Septina Primawati Rusli. Researchers used survey instruments with a questionnaire to 100 Muballigh in Pekanbaru City. The researchers conducted more in-depth interviews. The results showed that first, according to Islam, women should not be leaders, women could be leaders, if women have capabilities, women may be leaders absolutely. Second, the preachers of Riau argued on fifteen themes, The nature of menstruation, pregnancy, until women were not strong in leadership. Third, the arguments of Islamic law are the Koran, Hadith, ijma ', qiyas, and justice and gender equality in Islam.